'History taught in the pageant way': education and historical performance in twentieth-century Britain. Issue 2 (4th March 2019) - Bartie, Angela; Fleming, Linda; Freeman, Mark; Hulme, Tom; Hutton, Alexander; Readman, Paul
ABSTRACT: Historical pageants were important sites of popular engagement with the past in twentieth-century Britain. They took place in many places and sometimes on a large scale, in settings ranging from small villages to industrial cities. They were staged by schools, churches, professional organisations, women's groups and political parties, among others. This article draws on contemporary studies of heritage and performance to explore the blend of history, myth and fiction that characterised pageants, and the ways in which they both shaped and reflected the self-image of local communities. Pageants were important channels of popular education as well as entertainment and, although they are sometimes seen as backward-looking and conservative spectacles, this article argues that pageants could be an effective means of enlisting the past in the service of the present and future.